Clinical Implications and Risk Factors of Acute Pancreatitis after Cardiac Valve Surgery - Chung, Joo Won; Ryu, Sung Ho; Jo, Jung Hyun; Park, Jeong Youp; Lee, Sak; Park, Seung Woo; Song, Si Young; Chung, Jae Bock (Yonsei medical journal, 2013)
Acute pancreatitis is one of the potentially lethal complications that occurs after cardiac surgery. We tried to identify risk factors for and the prognosis of acute pancreatitis after cardiac valve surgery with cardiopulmonary bypass. We retrospectively analyzed a database of consecutive patients who underwent cardiac valve surgery with cardiopulmonary bypass between January 2005 and April 2010 at our institution. Patients were classified as having acute pancreatitis based on serum lipase concentration and clinical symptoms (lipase ≥ 180 U/L or ≥ 60 U/L with relevant symptoms). Of the 986 patients who underwent cardiac valve surgery with cardiopulmonary bypass, 58 (5.9%) patients developed post-operative pancreatitis. Post-operative hospital stay was significantly longer (29.7 ± 45.6 days vs. 12.4 ± 10.7 days, p = 0.005) and in-hospital mortality rate was higher (15.5% vs. 2.0%, p<0.001) in patients with post-operative pancreatitis than those without. Hypertension, chronic kidney disease, and peri-operative use of norepinephrine were identified as independent risk factors for developing pancreatitis after cardiac valve surgery. We found that acute pancreatitis after cardiac valve surgery requires longer hospitalization and increases the in-hospital mortality rate. Clinicians should be aware that patients could develop pancreatitis after cardiac valve surgery, especially in patients with hypertension and chronic kidney disease treated with norepinephrine.